Productivity in distribution - George, Kenneth D. (London, Cambridge U.P., 1966)
This study is a composition of sales, characteristics of the labor force, labor productivity, are compared between towns of different sizes and between towns having a similar size of market.
Occasional paper
Bibliographical footnotes.
osc 06/03/2019
Loans
Keywords: Retail trade